Perceived Risk and Online Shopping Behavior: Evidence from Karnali Province - Rawat, Dipak Singh; KC, Harendra (Journal of Entrepreneurship & Management Studies, 2024)
The burgeoning popularity of online shopping has not entirely mitigated consumer concerns. A significant segment of the customer base remains apprehensive about apparent risks associated with online transactions. This apprehension can lead to purchase aversion, hindering full participation in the e-commerce landscape. This study investigates the impact of perceived risk on online shopping behavior. In particular, the study investigates the effects of security and privacy risk, product quality and authenticity risk, financial risk, delivery and fulfilment risk and social risk on online shopping behavior. Therefore, the researchers employed an explanatory research design followed by positivist research philosophy. The population of the study was recognized as the entire number of online shoppers in Surkhet. This study adopted survey approach to collect data from a sample of 408 participants selected through convenience sampling. Five hypotheses were formulated and examined using multiple regression analysis with SPSS software. The result showed that security and privacy risk, product quality and authenticity risk, financial risk, delivery and fulfilment risk affects online shopping while social risk were non-significant at 0.05 level of significant. This research offers valuable information for businesses, policymakers, and those involved in the field (practitioners) to create plans (strategies and policies) that tackle concerns (perceived risk factors) people have about online shopping. This could lead to a more positive environment for online shopping use in Karnali Province.